Perilaku Sikat Gigi Terhadap Terjadinya Karies Gigi Di Sekolah Dasar - Santoso Budi Rohayu; Kursin Suli (Universitas Malahayati Lampung, 2022)
ABSTRACT: THE BEHAVIOR OF BRUSHING THE TOOTH ON THE OCCURRING OF DENTAL CARRIES IN ELEMENTARY SCHOOL Introduction: Dental caries can attack all walks of life in all age groups regardless of gender and social status. One of the age groups that often experience this disease problem is the elementary school age group.Purpose: This study aims to determine the facts of knowledge and behavior of elementary school children about brushing their teethMethod: This type of research is descriptive with a qualitative approach; The sampling technique used a total sample with data collection using in-depth interview techniques. Respondents in this study were students in grades 4, 5, and 6, totaling 6 studentsResult: This study found students had good knowledge about brushing their teeth but of students suffered from dental caries. Brushing teeth has become a daily routine and understand the purpose of brushing your teeth so that your mouth doesn't smell bad, you don't have bacteria, and your teeth are clean. not damaged, or cavities and tooth brushing frequency. 17.6% of respondents know the process of using toothpaste and using it when brushing their teeth but 5.9% of respondents do not know the function of toothpaste.Conclusion: the knowledge of elementary school students about the benefits of brushing their teeth is good, but the behavior of how to brush their teeth, the function of toothpaste is still not optimal. We suggest that the role of teachers and parents is needed in improving the knowledge and behavior of elementary school students in oral hygiene habits. Keywords : Brushing teeth, toothpaste, caries INTISARI: PERILAKU SIKAT GIGI TERHADAP TERJADINYA KARIES GIGI DI SEKOLAH DASAR Pendahuluan: Karies gigi dapat menyerang semua lapisan masyarakat pada semua kelompok umur tanpa memandang jenis kelamin dan status sosial. Salah satu kelompok usia yang sering mengalami masalah penyakit ini adalah kelompok usia sekolah dasar.Tujuan: Penelitian ini bertujuan untuk mengetahui fakta pengetahuan dan perilaku anak sekolah dasar tentang menggosok gigiMetode: Jenis penelitian ini adalah deskriptif dengan pendekatan kualitatif; Teknik pengambilan sampel menggunakan sampel total dengan pengumpulan data menggunakan teknik wawancara mendalam. Responden dalam penelitian ini adalah siswa kelas 4, 5, dan 6 yang berjumlah 6 siswaHasil: Penelitian ini menemukan bahwa siswa memiliki pengetahuan yang baik tentang menyikat gigi tetapi menderita karies gigi. Menyikat gigi sudah menjadi rutinitas sehari-hari dan memahami tujuan menyikat gigi agar mulut tidak bau, tidak ada bakteri, dan gigi bersih. tidak rusak, atau gigi berlubang dan frekuensi menggosok gigi. responden mengetahui proses penggunaan pasta gigi dan penggunaannya saat menyikat gigi tetapi responden tidak mengetahui fungsi pasta gigi.Kesimpulan: Pengetahuan siswa sekolah dasar tentang manfaat menggosok gigi sudah baik, namun perilaku cara menggosok gigi, fungsi pasta gigi masih belum optimal. Disarankan bahwa peran guru dan orang tua sangat diperlukan dalam meningkatkan pengetahuan dan perilaku siswa sekolah dasar dalam kebiasaan kebersihan gigi dan mulut. Kata kunci: Menyikat gigi, pasta gigi, karies